Pemberdayaan Keluarga dalam Meningkatkan Self Care Pasien Gagal Ginjal Kronik (GGK) di Daerah Lahan Kering Kepulauan (Genitri: Jurnal Pengabdian Masyarakat Bidang Kesehatan, 2023)
As many as 90% of CRF patients choose Hemodialysis (HD) therapy to maintain theirlives. HD treatment is closely related to the patient's quality of life. Family is the closest figurein providing care for CRF patients. The results showed that the family support has impact to increasing the quality of life. This is in the form of attitudes, actions, family acceptance ofpatients, motivational and encouraging, and providing help with sincerity. Empowerment tothe families of CRF patients is carried out through education and psychological assistance.This is intended to provide a clearer understanding that the needs of CRF patients with HD arein a hypersensitive state from all aspects. Their condition of despairing is the main cause oftheir struggle to do self-care. Intense and optimal social support from the family brings hopeand a positive attitude to CRF patients. This encourages patient confidence to recover by doingoptimal self-care such as maintaining diet, resting patterns, good stress management, maintainhealth control routine, exercising and routinely undergoing HD therapy. Patients will happy tofollow this routine because they feel meaningful to their family and others.
Keywords: Family Empowerment; Self Care; HD Patient